DO INSTITUTIONS MITIGATE THE RISK OF NATURAL RESOURCE CONFLICTS?. (1st November 2016) - O'Reilly, Colin; Murphy, Ryan H.
Abstract : The resource curse, as manifested by an increased likelihood of conflict over rents, can be mitigated by institutions. Lei and Michaels find that discoveries of "giant" oil fields increase the likelihood of violent conflict, but they find no evidence that democratic institutions mitigate this risk. We test whether institutions mitigate the resource curse by reducing the risk of natural resource conflicts. Our results indicate that high quality economic institutions reduce the likelihood of territorial (separatist) conflicts following natural resource rent windfalls. Highly autocratic and highly democratic institutions also reduce the likelihood of territorial conflict after natural resource rent windfalls. ( JEL Q34, O13, P48, D74)